1999
DOI: 10.1136/pgmj.75.883.285
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic approach to patients with suspected pulmonary embolism: a report from the real world

Abstract: SummaryThis study was carried out to examine the diagnostic approach to patients with suspected pulmonary embolism (PE) in a university hospital. A retrospective case record review of 251 patients with suspected pulmonary embolism was carried out according to a standard protocol, which looked at the utilisation of imaging techniques and compared clinical diagnoses with a standardised diagnosis established according to current recommendations. Isotopic lung scan was the most commonly used technique (73%), follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0
3

Year Published

1999
1999
2005
2005

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 15 publications
(2 reference statements)
0
5
0
3
Order By: Relevance
“…Its protean presentations coupled with complex diagnostic pathways contribute to this feeling. Recent studies suggest that complete investigations to confirm or exclude the diagnosis often don’t occur 1–6 . In my own institution a recent review of 400 cases revealed that fewer than 50% of cases had a definitive diagnosis made after an initial test for PE.…”
Section: Misdiagnosis Of Pulmonary Embolismmentioning
confidence: 99%
“…Its protean presentations coupled with complex diagnostic pathways contribute to this feeling. Recent studies suggest that complete investigations to confirm or exclude the diagnosis often don’t occur 1–6 . In my own institution a recent review of 400 cases revealed that fewer than 50% of cases had a definitive diagnosis made after an initial test for PE.…”
Section: Misdiagnosis Of Pulmonary Embolismmentioning
confidence: 99%
“…The rate of pulmonary angiography performed in these patients is typically less than 12%, however, with most physicians unwilling or unable to obtain angiography routinely in the workup of PE [24,78,79,86,87]. Some authors believe that failure to obtain angiography in all cases that have nondiagnostic studies is unacceptable due to the likelihood of missed pulmonary emboli.…”
Section: Diagnostic Approachmentioning
confidence: 99%
“…Sir, The observation that patients with indeterminate isotope lung scans received anticoagulant therapy without the benefit of validation or refutation of pulmonary thrombo-embolic disease through the use of investigative modalities for lower limb deep vein thrombosis,1 resonates with my own observation that there is widespread underutilisation of the principle of a ‘one stop’ facility for streamlining investigation and treatment of common disorders. A ‘one stop’ facility for investigation of pulmonary thrombo-embolic disease would have ensured that patients with indeterminate isotope lung scans could proceed to an investigative evaluation of the lower limbs for deep vein thrombosis at the same sitting.…”
mentioning
confidence: 99%
“…The generalisability of this principle is exemplified by the investigation of the underlying cause of iron deficiency anaemia in a ‘one stop’ facility utilising upper gastrointestinal endoscopy and colonoscopy at the same sitting, resulting in one of the highest yields for identification of multiple pathology as the aetiopathogenetic basis of this disorder,2 and also reducing the likelihood of delayed recognition of ‘clinically silent’ underlying causes such as left-sided colonic cancer 3. The authors also addressed the issue of suboptimal concordance between contrast venography and ultrasonography for detection of lower limb deep vein thrombosis, including above knee involvement 1. A related issue is that of the strength of the negative predictive value of compression ultrasonography of lower limb veins.…”
mentioning
confidence: 99%